Exploring how language learning platforms on Instagram and TikTok can facilitate collaborative foreign language learning experiences of undergraduates - khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
Social media has remained one of the most impactful technological advancements in enhancing learners ‘leaners’ collaboration and increasing performance and proficiency in foreign language education. TikTok and Instagram content have been particularly proven to enhance the collaborative experiences of foreign language learners, as they enhance their productivity when they work as a team. In this paper, the focus was to expand the study on how language learning platforms on Instagram and TikTok can be leveraged to enhance the collaborative learning experiences of foreign language undergraduates. The study participants included 62 undergraduates who participated in the experiment and 113 FL undergraduates who participated in the survey. The experiment involved the administration of a series of group tasks using Instagram Reels and TikTok short videos. The survey was conducted using a digitally designed questionnaire. The result of the pretest indicated that during the pretest phase, participants in both the control group (CG) and the experimental group (EG) demonstrated similar degrees of collaboration in the context of enhancing foreign language proficiency. By highlighting the significant influence of using TikTok short videos and Instagram Reels, the post-test findings reveal that the EG performed much better than the CG in terms of collaborative experiences for learning foreign languages. Given that the EG had a significantly higher mean cooperation score of 73.83 in comparison to the CG’s mean score of 54.32, the t-value of 18.63 (p < 0.001) provides further evidence that the EG’s score is much higher. In the survey, the responses to three statements indicate that a significant proportion of respondents strongly agree (SA) or agree (A), ranging from 82.60% to 93.36%, that these platforms effectively contribute to overall language learning performance, enhance collaborative language learning, and improve academic outcomes.